Belongingness And Love In David Nicholls' One Day Novel (2009): A Humanistic Psychological Approach - Yulianti, Denny; , Drs. H Abdillah Nugroho M.Hum; , Nurhidayat, S.Pd (2013)
The mayor problem of this study is Dexter Mayhew who needs love and care from Emma Morley. The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on Humanistic Psychological Approach. In analyzing One Day story the researcher uses qualitative method and Humanistic Approach. The object of the study is David Nicholls's One Day, published by Hodder and Stoughton, 2010. The data sources are primary data and secondary data. The primary data source is the novel One Day itself and the secondary data sources are the other sources related to the analysis such as the author's biography, the book of fiction, the book of humanistic, dictionary, virtual references, and the other relevant information that support this research. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive qualitative. Based on the analysis above, the researcher draws the following conclusions: first, the researcher concludes that the elements of the novel present a good unity that consists of exposition, complication, climax, and resolution; second, Love and care of Emma Morley are very needed by Dexter Mayhew. Keywords: One Day, Humanistic Psychological Approach, Love and Belongingness.